Using first-contact serum ferritin to predict severe thrombocytopenia in dengue patients: determination and validation in independent cohorts. Issue 6 (3rd June 2022) - Lodha, Abhijit; Pillai, Ashwin; Reddy, Pavan; Munshi, Nita
Abstract: Background: Severe thrombocytopenia and associated haemorrhage are dreaded complications of dengue fever. The identification of a biomarker that can predict, or rule out, its subsequent development can help identify at-risk individuals. Methods: 200 dengue patients were included – the first 100 in the deterministic cohort and the latter, the validation cohort. Serum ferritin levels were measured at first presentation. Platelets were monitored serially. Data from the first cohort was used to determine the optimal ferritin level to predict significant thrombocytopenia (<20, 000/µL). This threshold was validated in the second cohort. Results: In the deterministic cohort, a ferritin threshold of 593 ng/mL predicted severe thrombocytopenia with a sensitivity of 93.33%, negative predictive value of 98.18% and negative likelihood ratio (LR-) of 0.10. In the validation cohort, the sensitivity and negative predictive value of this threshold were both 100%. The power of the study (determined post-hoc) for each cohort was 98.4% and 86.4% respectively. Conclusion: First-contact ferritin consistently identified at-risk individuals. Individuals with ferritin levels below 593 ng/mL were unlikely to develop severe thrombocytopenia independent of clinical presentation.